The gods will not save you: Greek culture and mythology in The Wire - San Julián Alonso, Raúl (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Within the pantheon of the great television series of recent decades, "The Wire" (D. Simon & E. Burns, HBO, 2002-2006) undoubtedly occupies a prominent place for critics and audiences. “The Wire”, disguised as a police thriller, is a serial story that stands out for its cyclical structure, tragic archetypes and a choral look that makes the difference from the rest of current television content. Three characteristics (the corality, the tragedy, and the cyclical time) that make up the essence of Greek theater. And as soon as we start analyzing The Wire we see what is hidden in the characters and plots of one of the most prestigious series in history owe their essence to the cosmogony and Greek mythology, the root of all our culture.